Internship report in Community Pharmacy, an internship report in Hospital Pharmacy and a monograph entitled “Biomembrane-derived vesicles for improved cancer-targeted therapies: focus on cell and bacterial membranes, and extracellular vesicles”. - Santos, Soraia Cristina da Costa (2023)
Relatório de Estágio do Mestrado Integrado em Ciências Farmacêuticas apresentado à Faculdade de Farmácia